16. THE CONTINUOUS TRAINING RESULTS OF HANOI MEDICAL UNIVERSITY FROM 2015 TO 2020 AND THE PROFESSIONAL DEVELOPMENT TRAINING NEEDS OF HEALTHCARE PERSONNEL IN THE NEW SITUATION (Vietnam Journal of Community Medicine, 2023)
Objective: The study aimed to describe the outcomes of the continuous training conducted by the Hanoi Medical University from 2015 to 2020 and the professional development needs of healthcare professionals in the new context. Methods: The research utilized quantitative and qualitative methods, analyzing data from 13,893 training records and conducting indirect interviews with 153 former trainees through self-administered questionnaires and in-depth interviews with seven alums from the training center based on societal demands.Result: The results showed that during the 2015-2020 period, the Training Center organized many diverse continuous training programs to meet societal demands. The demand for continuous training for healthcare professionals has been increasing regarding content, training methods, and organization.Conclusion: The growing demand for training presents opportunities and challenges for the Training Center to improve and further develop continuous training programs to meet the increasing needs of healthcare professionals and medical facilities nationwide in the new context.
Keywords: Continuous training, CME (Continuing Medical Education), training demand, Hanoi Medical University.